Effects of rotation speed and dwell time on the mechanical properties and microstructure of dissimilar aluminum-titanium alloys by friction stir spot welding (FSSW)Effekte von Rotationsgeschwindigkeit und Verweilzeit auf die mechanischen Eigenschaften und das Gefuge von Aluminium-Titan-Legierungen durch artfremdes Ruhrreibpunktschweissen - Asmael, M. B. A.; Glaissa, M. A. A. (Wiley-V C H Verlag Gmbh, 2020)
In this study, the effects of rotation speed and dwell time on the mechanical properties and microstructure of friction stir spot welded joints of dissimilar aluminum and titanium alloys were investigated. Aluminum AA6061 and titanium Ti-6Al-4 V alloys were selected as the work piece. The joint quality, mechanical behavior, and microstructural evolution in the welded regions were considerably affected by the welding parameters. The results of scanning electron microscopy showed the formation of Ti3Al intermetallic compounds near the thermomechanical affected zone, which significantly affected the properties of the welding joint. Maximum tensile shear load was produced at 1000 min(-1)and 10 s dwell time. Moreover, the welding joint microhardness was improved with increasing the rotation speed.
Keywords: Friction stir spot welding; aluminum alloy; titanium alloy; lap joint; welding parameters